2015
DOI: 10.1179/1743282015y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

New national and regional bryophyte records, 43

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…So far, it has been known to be widely distributed in southern South America where it is relatively frequent along the western coast of the continent, ranging from the Argentinean Neuquén and Chilean Cautin Provinces to Tierra de Fuego and extending to the northern maritime Antarctic (Deception Island) and subantarctic South Georgia (Bell, 1974;Ochyra et al, 2008a,b). The species subsequently recurs on the Prince Edward Islands and Îles Crozet (Blockeel et al, 2008), Îles Kerguelen (Cardot, 1916) and Heard Island (Ellis et al, 2015b), as well as on the Île Amsterdam in the warm-south-temperate zone (Ellis et al, 2015a). The present discovery of B. pachydictyon on Tristan da Cunha fills an obvious gap in the range of this species and confirms its phytogeographical status as an amphiatlantic southtemperate species.…”
supporting
confidence: 67%
“…So far, it has been known to be widely distributed in southern South America where it is relatively frequent along the western coast of the continent, ranging from the Argentinean Neuquén and Chilean Cautin Provinces to Tierra de Fuego and extending to the northern maritime Antarctic (Deception Island) and subantarctic South Georgia (Bell, 1974;Ochyra et al, 2008a,b). The species subsequently recurs on the Prince Edward Islands and Îles Crozet (Blockeel et al, 2008), Îles Kerguelen (Cardot, 1916) and Heard Island (Ellis et al, 2015b), as well as on the Île Amsterdam in the warm-south-temperate zone (Ellis et al, 2015a). The present discovery of B. pachydictyon on Tristan da Cunha fills an obvious gap in the range of this species and confirms its phytogeographical status as an amphiatlantic southtemperate species.…”
supporting
confidence: 67%
“…At the second our study of holotype and isotype of N. japonica showed that it does not agree with plants named as N. japonica by Furuki. After wards we found that N. lescurii in the description provided by Furuki (1997) (and also plants reported under this name in Ellis et al 2015) is well agreed with plants in the types of N. japonica. Therefore the plants bearing smoothsurfaced, ho mo ge nous oilbodies belong to another taxon.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 57%
“…as closely related to N. japonica, but particularly diffe rent in coarsely granulate oil bodies. After, Bakalin (Ellis et al 2015) uncritically used oilbodies characteristics and reported N. lescurii for Magadan Province in North East Asia. To ana lyze the differences and various (geographical, morphological, ecological) relationships between N. japonica and N. lescurii were the main goal of the present account.…”
Section: A Note On Nardia Japonica Steph (Gymnomitriaceae) I N T R Omentioning
confidence: 99%
“…The best example is Lithuania, which has relatively poor moss flora because of the natural conditions prevailing in this small country, especially the lack of natural rock outcrops. In 2003, some 335 species have been recorded in Lithuania [59], but since then no fewer than 20 species have been added, including the present record of Splachnum pensylvanicum [60][61][62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%